THE INNER STRUCTURE OF COPPER FROM THE VENDIAN VOLCANOSEDIMENTARY ROCKS OF VOLYN’ - KVASNYTSIA, I.; KOSOVSKYI, Ya.; SHUNKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The data of inner structure of native copper from occurrences of Volyn’ (the vendian volcanosedimentary rocks) are studied. The simple and polysynthetic twins under spinel law for different morphological types of native copper, sectors of complex twins of crystals of native copper have been determined.